STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.H UMUR 21 TAHUN DI PUSKESMAS WATUMALANG WONOSOBO - Fitria, Khululu Ngainil; Resmi, Dewi Candra; Alfiah, Nur; Setiani, Fibrinika Tuta (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Objective: Providing comprehensive midwifery care according to midwifery service standards with SOAP documentation. Methodology: The method in taking this case is with a descriptive approach and midwifery management in Continuity of Care on Mrs. H aged 21 years at the Watumalang Wonosobo Health Center from March 9, 2024 to May 3, 2024. Results: The method in taking this case is with a descriptive approach and midwifery management in Continuity of Care on Mrs. H aged 21 years at the Watumalang Wonosobo Health Center from March 9, 2024 to May 3, 2024. Conclusion: Based on the assessment of comprehensive midwifery care, complications were found in pregnancy, namely placenta previa. Midwifery care for pregnant women with placenta previa carried out on Mrs. H aged 21 years has received treatment and management in accordance with midwifery care standards.